Numerical Analysis of Unsteady Cavitating Vortex around Two-dimensional Wedge-shaped Submerged Body - Ji-Hye Kim; So-Won Jeong; Byoung-Kwon Ahn; Chul-Soo Park; Gun-Do Kim (한국해양공학회지, 2018)
Unlike a slender body, vortices are shed off alternately in the wake of a blunt body. In the case of liquid flows, when the pressure falls below the vapor pressure, cavitation occurs in the vortex core and affects the formation of the vortex street. This phenomenon is of major importance in many practical cases because the alternate shedding of vortices creates imbalanced forces on the body. Hence, it is very important to determine the shedding frequency of cavitating vortices. In this paper, the unsteady cavitating flow around a two-dimensional wedge-shaped submerged body was simulated using the commercial code STAR-CCM+. A numerical investigation of the structure of cavitating vortices was performed for a model with an apex angle of 20°. The results were validated by comparing them with experimental measurements carried out at a cavitation tunnel of Chungnam National University (CNU-CT). It was found that the shedding frequency of the vortex increased by up to 18%, which was strongly affected by the development of cavitation.